2005
DOI: 10.1111/j.1582-4934.2005.tb00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction between SNAP-23 and L-type Ca2+channel

Abstract: Atomic force microscopy (AFM) in combination with electron microscopy (EM) and biochemical approaches, has helped in the discovery of the fusion pore or porosome at the cell plasma membrane, where secretory vesicles dock and fuse to release their contents [1][2][3][4][5][6][7]. The structure of the porosome in both exocrine [1,2,5,6], neuroendocrine cells [3,4], and in neurons [7], at nanometer-subnanometer resolution, and its dynamics in real time, have been determined. Immunochemical studies further demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…This prompt mobilization of Ca 2+ is essential for many physiological functions, such as the release of neurotransmitters. Not surprisingly, calcium ion channels have been found in direct association with t-SNARE (SNAP-23), at the base of fusion pores or porosomes (permanent supramolecular structures at the cell plasma membrane [12][13][14][15][16][17][18][19]), where secretory vesicles dock and fuse to release their contents [20]. Calcium ion [Ca 2+ ] exists in its hydrated state within cells [11].…”
Section: Molecular Mechanism Of Snareinduced Membrane Fusionmentioning
confidence: 99%
“…This prompt mobilization of Ca 2+ is essential for many physiological functions, such as the release of neurotransmitters. Not surprisingly, calcium ion channels have been found in direct association with t-SNARE (SNAP-23), at the base of fusion pores or porosomes (permanent supramolecular structures at the cell plasma membrane [12][13][14][15][16][17][18][19]), where secretory vesicles dock and fuse to release their contents [20]. Calcium ion [Ca 2+ ] exists in its hydrated state within cells [11].…”
Section: Molecular Mechanism Of Snareinduced Membrane Fusionmentioning
confidence: 99%
“…Exocytosis of preformed mediators in MCs after FcεRI activation has been described to require the phosphorylation of Ser 120 and Ser 95 of SNAP-23 (43), and it has been shown that all the SNAP-23 bound to syntaxin 4 in the plasma membrane during exocytosis in RBL2H3 cells is phosphorylated (43). Interestingly, evidence indicates that SNAP-23 mediates the docking of secretory granules at low Ca 2+ levels (100 nM) by interacting with different members of the synaptotagmin family (44) and that SNAP-23 can associate with L-type Ca 2+ channels (45). Further analysis on the participation of SNAP-23 on secretion of preformed mediators in MC stimulated with different ligands will shed light on the mechanism behind rapid exocytosis of mediators in the absence of massive Ca 2+ mobilization or degranulation in MCs.…”
Section: Mechanism Of Tlr4-induced Tnf Secretion In Bmmcsmentioning
confidence: 99%
“…Porosome size ranges from 100 to 180 nm in pancreatic acinar cells to ~12 to 17 nm in neurons and astrocytes. Several proteins constitute the porosome complex (51), including structural proteins such as actin, ion channels such as the chloride and calcium channels (51,18), and the t-SNARE membrane fusion proteins located at its base (60), where secretory vesicles transiently dock and fuse to expel their contents. During cell secretion, the porosome opening dilates to allow release of secretory products, returning to its resting size following completion of the process (13,15,97).…”
mentioning
confidence: 99%